Synthesis and kinetic studies of mutual azo prodrugs of 5-aminosalicylic acid with sulfamethoxazole and trimethoprim as models for colon targeting - Yasser Fakri Mustafa (University of Mosul, 2010)
In this study, two mutual azo prodrugs were synthesized for colon targeting in a treatment of colonic diverticular disease. The first was synthesized by coupling sulfamethoxazole with salicylic acid; the second was synthesized by coupling one mole of trimethoprim with two moles of salicylic acid. In vitro kinetic studies of these mutual prodrugs in hydrochloric acid buffer (pH 1.2) and in phosphate buffer (pH 7.4) were monitored. Hydrolysis of these mutual prodrugs was established in rat fecal matter. The release of 5-aminosalicylic acid and sulfamethoxazole or trimethoprim from these mutual prodrugs was almost complete and it followed first order kinetics. The prodrug approach to drug physico-chemical properties modification based on enzyme specifications may offer a new approach for improving drug product efficacy and reducing most of its adverse effects.